Reliability Test on Vienna Rectifier for Wide Bandgap Devices in EV Charging Systems - Bharaneedharan Balasundaram; P. Suresh; Parvathy Rajendran; It Ee Lee; C. Ahamed Saleel (IEEE Access)
This study examines the reliability of several electronic components in a Vienna Rectifier configuration, which is a critical topology for power conversion systems. Component selection has become increasingly important over the past few years since the power electronics of today demand more efficiency, power density, and operational reliability. Extreme reliability testing such as temperature cycling, electrical overload, and long duration of high-frequency operation was a part of the study. GaN MOSFETs had an edge over Si and SiC MOSFETs in several aspects, such as decreased conduction and switching losses, better thermal management, and more consistent performance with time. While GaN MOSFETs performed better in general and especially at high frequencies and temperatures, SiC MOSFETs showed some improvements over the conventional Si devices. Capacitors, diodes, MOSFETs, and inductors are put to test for reliability under different stress conditions. The combination of diodes and GaN MOSFETs showed a synergistic effect in improving system dependability and reducing temperature-induced degradation. This is a significant result. The combined effects allowed active and passive parts to last longer and function more reliably. These results open insights into selecting components for systems in the automotive and aerospace industries, which mostly rely on reliability.